T54. The difference of contralateral motor overflow according to spasticity among people with stroke. (May 2018) - Shin, Joon-Ho; Lee, Ji-Yeong; Song, Won-Kyung; Koh, Kyung; Shim, Jae Kun
Abstract : Introduction: Contralateral motor overflow is known as overt involuntary movement from accompanied contralateral production of voluntary movement. The prevalence of motor overflow is high in patients with stroke. Many previous studies were reported, however there is lack of studies about the relationship between motor overflow and spasticity or musculoskeletal factor. The objective of the present study was to investigate the contralateral motor overflow in patients with stroke during finger force production tasks in terms of spasticity and musculoskeletal factor. Methods: Forty-four patients with stroke, and 20 healthy control were participated in this study. Participants were seated and requested to put all fingers of both hands on force sensors (FUTEK) with various musculoskeletal factors (wrist posture: flexed, neutral, and extended posture) and speed (fast, slow). They produced maximum isometric pressing force with all fingers of right or left hand and the forces were recorded. We analyzed motor overflow magnitude, which is defined as the ratio of the non-task hand force to the corresponding task hand finger force. The spasticity was graded as modified Ashworth scale and we define that of healthy control as 0. Results: Motor overflow was different according to spasticity and the difference was consistent regardless of wrist posture and speed (all, p  < 0.05). In addition, motor overflow was different depending on the finger flexion speed regardless of wrist posture (all, p  < 0.05). Conclusion: We conclude that contralateral motor overflow during maximum force production tasks is dependent on the spasticity and speed of finger flexion regardless of physical wrist posture. Therefore, contralateral motor overflow could result from upper motor neuron lesion other than musculoskeletal facots.